2022
DOI: 10.1108/ilt-07-2021-0274
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface topography on cavitation evolution of liquid film lubricated mechanical seals

Abstract: Purpose The purpose of this paper is to investigate the effects of surface topography, including surface roughness, waviness and taper, on the cavitation of liquid film lubricated mechanical seals (LFL-MS). Design/methodology/approach A universal governing equation considering cavitation is established, and an equivalent relative density is defined to characterize the cavitation degree. The equation is discretized by the finite volume method and solved by the Gauss–Seidel relaxation scheme. Findings Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Khatri and Sharma 27 investigated the impact of spherical-shaped texturing on the dynamic performance of a hole-entry hybrid bearing and reported the enhancement of threshold speed and dynamic coefficients for fully textured distribution. Furthermore, several studies [28][29][30][31][32][33][34][35][36][37] have shown that several geometrical flaws, non-circular bearings, different journal shapes, lobe bearings, curved bearings, surface texturing and so forth influence the bearing operation.…”
Section: Introductionmentioning
confidence: 99%
“…Khatri and Sharma 27 investigated the impact of spherical-shaped texturing on the dynamic performance of a hole-entry hybrid bearing and reported the enhancement of threshold speed and dynamic coefficients for fully textured distribution. Furthermore, several studies [28][29][30][31][32][33][34][35][36][37] have shown that several geometrical flaws, non-circular bearings, different journal shapes, lobe bearings, curved bearings, surface texturing and so forth influence the bearing operation.…”
Section: Introductionmentioning
confidence: 99%
“…Brunetière et al [23] analyzed the influence of the design and operating parameters on the thermo-hydrodynamic behavior of the mechanical end face seals in steady and dynamic tracking modes. To research the influence factors of cavitation starting and evolution, Li et al [24] analyzed the effects of different waviness amplitudes, numbers and tapers on the cavitation characteristics. The results indicated that the start and evolution of the cavitation were affected by both the waviness and radial taper, and the change of the cavitation region along the circumferential direction was influenced by the waviness, while that along the radial direction depended on the taper.…”
Section: Introductionmentioning
confidence: 99%